Noncoding RNAs regulate alternative splicing in Cancer - Yunze Liu (Journal of Experimental & Clinical Cancer Research, 2021)
Abstract AS (alternative splicing) is a fundamental process by which a gene can generate multiple distinct mRNA transcripts to increase protein diversity. Defects in AS influence the occurrence and development of many diseases, including cancers, and are frequently found to participate in various aspects of cancer biology, such as promoting invasion, metastasis, apoptosis resistance and drug resistance. NcRNAs (noncoding RNAs) are an abundant class of RNAs that do not encode proteins. NcRNAs include miRNAs (microRNAs), lncRNAs (long noncoding RNAs), circRNAs (circular RNAs) and snRNAs (small nuclear RNAs) and have been proven to act as regulatory molecules that mediate cancer processes through AS. NcRNAs can directly or indirectly influence a plethora of molecular targets to regulate cis-acting elements, trans-acting factors, or pre-mRNA transcription at multiple levels, affecting the AS process and generating alternatively spliced isoforms. Consequently, ncRNA-mediated AS outcomes affect multiple cellular signaling pathways that promote or suppress cancer progression. In this review, we summarize the current mechanisms by which ncRNAs regulate AS in cancers and discuss their potential clinical applications as biomarkers and therapeutic targets.